Financing for Development : Enhancing the Financial Safety Net for Developing Countries. (Policy Papers; Policy Paper ;, 2015)
Access to Fund financial resources provides a financial safety net to help countries manage adverse shocks, acting as a potential supplement to foreign reserves when there is a balance of payments need. Such support is especially important to developing countries with limited capacity to borrow in domestic or foreign markets. This paper proposes a set of measures that would expand access to Fund resources for developing countries, as one of the initiatives the Fund is undertaking as part of the wider effort of the international community to support countries in pursuing the post- 2015 Sustainable Development Goals (SDGs).